Oxypoda sylvia Casey 1906 ... - Klimaszewski, Jan; Chandler, Donald S.; Davies, Anthony; Bourdon, Caroline (Zenodo, 2023)
232. Oxypoda sylvia Casey (Illustrations in Klimaszewski et al. 2006, 2018), Table 1 References. Casey 1906, 1911 (as Moluciba grandipennis Casey). Seevers 1978. Klimaszewski et al. 2005a, 2006, 2011, 2015a (as Oxypoda grandipennis), 2018, 2020, 2021. Distribution. Nearctic, recorded from A/S (Klimaszewski et al. 2021). Canada: AB, BC, LB, MB, NB, NF, NS, ON, QC, SK, YT. USA: AK, ME, NH. Collection and Habitat data. In NH found in birch and fir litter, and in rotten wood. Most specimens were collected by flight intercept traps; specimen from mid-winter was taken by a pitfall trap. Collected from June to March; most specimens were taken during August–September. In AK specimens were captured in alpine tundra, as well as forests of mostly spruce, some aspen, and Betula sp. and Populus tremuloides; in old-growth, and thinned and unthinned 2nd growth forests (Klimaszewski et al. 2021). In Canada found in many forest types, including hardwood and various coniferous species; adults common in decaying and rotten ... : Published as part of Klimaszewski, Jan, Chandler, Donald S., Davies, Anthony & Bourdon, Caroline, 2023, Aleocharine rove beetles of New Hampshire, USA: new taxa and new records (Coleoptera, Staphylinidae, Aleocharinae), pp. 1-141 in Zootaxa 5364 (1) on pages 109-110, DOI: 10.11646/zootaxa.5364.1.1, http://zenodo.org/record/10145460 ...